Multifunctional biosynthesized magnetosome for multimodal imaging and combined therapy of tumor - Xiaoqing Han; Xingbo Wang; Jiao Yan; Panpan Song; Yanjing Wang; Yaqing Kang; Abdur Rauf; Haiyuan Zhang (Materials Today Bio)
The large recruitment of tumor-associated macrophages and low exposure of tumor-associated antigens in tumor microenvironment have severely suppress the efficacy of anti-tumor immunotherapy. Herein, biosynthesized magnetosome (Mag) from bacteria was loaded with photothermal/photodynamic agent/near infrared (NIR) fluorescence dye (IR780) and further modified with lipid-PEG-c(RGDyK) through biomembrane, forming IMagRGD for fluorescence imaging, magnetic resonance imaging, immunotherapy and photodynamic/photothermal therapy. After intravenous injection into B16F10 tumor-bearing mice, IMagRGD could efficiently accumulate in tumor tissues based on near infrared (NIR) fluorescence and magnetic resonance dual-modality imaging, and repolarize tumor-associated macrophages (TAMs) from M2 phenotype to M1 phenotype, significantly improving the effect of tumor immunotherapy. Moreover, photothermal and photodynamic effect of IR780 could kill tumor cells and elicit immunogenic cell death to mediate anti-tumor immunity, promoting dendritic cells (DCs) maturation and then activating specific effector T cells to further eliminate tumor cells. This study provides a new approach for reversing the activity of tumor immunosuppressive microenvironment and strengthening the efficiency of tumor photoimmunotherapy.